Enhancing water treatment with polyvinylidene fluoride (PVDF)/cellulose composite membranes : a comprehensive review - Perry Law, Nyuk Khui; Md Rezaur, Rahman; Khairul Anwar, Mohamad Said; Jehan Y., Al-Humaidi; Muhammad Khusairy, Bakri; Kuok, King Kuok; Raed H., Althomali; Muhammad Rafiq Mirza, Julaihi; Mohammed M., Rahman (Taylor & Francis, 2024)
This study delves into the critical examination of prior research on PVDF/cellulose membranes and their applicability in water treatment contexts. Raw water sources are typically laden with contaminants, organic compounds, soil particulates, and humic substances, all of which contribute to membrane fouling. The challenge escalates when membranes lack adequate hydrophilicity, resulting in heightened costs for water treatment, notably in regions with swampy or peaty water sources. Despite the potential of hydrophilic biopolymers like cellulose as a solution, their complex and crystalline structure poses handling difficulties. This review aims to deepen our understanding of the significant potential of PVDF/cellulose membranes as sustainable and effective solutions for water treatment. These membranes showcase promising attributes such as high water flux and straightforward production processes. Our goal is to promote the broader utilization of this widely available biopolymer to enhance the performance and sustainability of PVDF membrane filtration in water treatment applications.